Indigenous Microorganisms for Biodegradation of Household Detergents in Aquatic Bioremediation: A Meta-Scientific Review - Khaer, Ashhabul Kahfi; Arman, Putri Nabila Tsabitah; Malisan, Asri; Ardianto, Nurul Hikma; Ramlawati, Ramlawati; U, Sahrani (Jurnal Biologi Tropis, 2026)
Household wastewater containing detergent residues is a major source of aquatic pollution due to synthetic surfactants, particularly Linear Alkylbenzene Sulfonate (LAS) and Alkyl Sulfate (AS), which are toxic and resistant to natural degradation. Bioremediation using indigenous microorganisms offers an environmentally friendly and cost-effective alternative for degrading these pollutants. This narrative review evaluated the potential of indigenous microorganisms for biodegradation of household detergent residues and their prospects for aquatic bioremediation. Literature was systematically collected from Google Scholar, PubMed, and Scopus, including primary research articles published in Indonesian or English between 2018 and 2025. Twenty eligible studies were analyzed. The findings showed that Pseudomonas, Bacillus, Acinetobacter, Aeromonas, and Corynebacterium were the most frequently reported indigenous bacteria capable of degrading detergent surfactants and related organic compounds, with degradation efficiencies ranging from 7.7% to 100%, depending on microbial characteristics, substrate type, and environmental conditions. Bacterial consortia and biofilm-based systems consistently achieved higher degradation efficiencies than single isolates. Biodegradation primarily involves extracellular enzymes, including monooxygenases, sulfo-transferases, and amidases, which convert surfactants into less harmful compounds. Despite most studies being limited to laboratory-scale experiments, indigenous microorganisms demonstrate strong potential as sustainable bioremediation agents. Future research should focus on consortium optimization, molecular characterization, and field-scale validation to improve practical implementation in aquatic environments.